VD_FINDINFO HC / 2012 / 365 vom 4. Juni 2012 - VD Tribunal cantonal (2012)
RÉSILIATION ANTICIPÉE, DEMEURE, SOMMATION, EXPULSION DE LOCATAIRE | 257d CO, 266n CO, 257 CPC (CH), 312 al. 1 CPC (CH), 314 al. 1 CPC (CH)